Bibliometric analysis of levosimendan - Xian-Shu Zhao; Yi-Ping Yu; Yun-Tai Yao (International Journal of Cardiology: Heart & Vasculature)
Background: Levosimendan (LEVO), a calcium sensitizer and adenosine triphosphate-dependent potassium channel opener, has been widely used for decades in medical and surgical patients for advanced heart failure (HF), right ventricular failure, cardiogenic shock, takotsubo cardiomyopathy, pulmonary hypertension, and so on. Currently, as the limited scope and lack of comprehensive data in current LEVO publications, there is an increasing obstacle to conducting new studies that require integrated information and quantifiable results. Thus, the current study was performed to identify the research trends and hot spots in LEVO-related publications using bibliometric software. Methods: LEVO-related publications from 1990 to 2023 were searched and retrieved in the Web of Science Core Collection (WoSCC) and analyzed with VOSviewer, CiteSpace, Scimago Graphica, R-bibliometrix and Rstudio for publication dates, countries/regions, institutions, authors, keywords, journals, and references. Results: Finally, a total of 1,432 LEVO-related articles were included in the present study. Annual LEVO-related publications have been increased yearly. The United States was the most productive country with 243 articles. The University of Helsinkin published 69 articles in the field of LEVO, which were the most productive institution among all the institutions. Of all the authors, professor Pollesello,Piero was the most productive author with 62 articles. Moreover, the results of the co-citation analysis and citation bursts analysis revealed that the safety and effectiveness of LEVO were the global research trends and potential hot spots. Conclusions: This study systematically summarizes the current status in the field of LEVO and provides insights into the research focuses and future hotspots.